The 4Cs Learning Model in Teacher Professional Development Program - Sunardi Sunardi; Ferry Doringin (Humaniora, 2020)
The research aimed to analyze the effectiveness of 4Cs models (communication, collaboration, critical thinking and problem-solving, as well as creativity and innovation) to improve teachers’ performance in the 21st-century era. The development of technology in the era, especially in the way of learning of students, was responded to lately by schools and teachers. Using a qualitative case study, the research analyzed the school’s professional development program using the 4Cs model. The research result shows that the model of 4Cs gives enthusiasm, and a deep impression on teachers in their classroom activities accelerates the competences of teachers in using technology. Besides, it shows the level of importance of the model: communication, then creativity, collaboration, and critical thinking. The research has limitations in assessing the performance of students who are taught by trained teachers. So, further research is proposed to analyze the performance of students regarding the 4Cs competences.